Using a Memory-Based Strategy for Vocabulary Instruction via Online Games to Enhance the Vocabulary Size of Secondary School Students - Honboonherm, Wipasinee; Sukavatee, Pornpimol (An Online Journal of Education, 2024)
The objectives of this research were: 1) to explore the effect of a memory-based strategy for vocabulary instruction via online games on enhancing vocabulary size, and 2) to investigate students’ opinions on this memory-based strategy for vocabulary instruction via online games. The participants of this study were 37 tenth-grade students from a public school in Chiang Rai province, selected through purposive sampling. The research instruments included lesson plans with vocabulary online games corresponding to each step of the memory-based framework. Online audio flashcards were used in the first step to introduce new words. Matching pairs and finding a match were employed in the second step to understand the meanings of the words. In the third step, anagrams and crosswords were used to link the meanings of the words with their forms. In the final step of consolidating the words, quiz games were implemented. Vocabulary size was assessed through pre and post-tests, student reflections, and semi-structured interviews. Analysis using paired sample t-tests, mean, standard deviation and content analysis revealed that students’ scores after using the memory-based strategy (M = 14.76, SD = 4.28) significantly increased from their pre-test scores (M = 9.22, SD = 3.07), with statistical significance at the .05 level. Additionally, students expressed positive opinions about the memory-based strategy for vocabulary instruction via online games. This research found that the strategy can be effectively used to increase vocabulary and can be adapted for other learning topics. The study also highlights that learning English vocabulary becomes more enjoyable and memorable, particularly through matching games that pair words with images, aiding in acquiring new vocabulary more effectively.